An in silico study on reproposing eravacycline as an MMP inhibitor - Deepthy Varghese, Dhilna Sunny, Anna Kurian, Tom Cherian, Leyon Varghese (Journal of Applied Pharmaceutical Science, 2023)
Considering the role of matrix metalloproteinases (MMPs) in various pathological conditions, including cancer, they are investigated as good targets in present-day drug discovery. Tetracycline antibiotics are already being repurposed for their anticancer activities. Here, we made an investigation on some tetracycline compounds, such as demeclocycline, eravacycline, lymecycline, and omadacycline by analyzing their binding affinity with two groups of MMPs, viz, collagenases and gelatinases using in silico approach. The ΔG values of the interaction of eravacycline with different MMPs range from −8.6 Kcal/mol for MMP1 to −9.7 Kcal/mol for MMP9 indicating strong binding affinity. Further molecular dynamic simulation studies revealed that the MMP9-eravacycline interactions are highly stable and durable in virtual physiological conditions. Out of the four tetracyclines analyzed, eravacycline showed a strong broad-spectrum inhibitory potential against all the collagenase and gelatinase enzymes. This antibiotic is, therefore, recommended for further in vitro and pre-clinical validation studies to promote its repurposing in clinics.
Keywords: Collagenases, eravacycline, gelatinases, MMPs, reproposing, tetracyclines